- RC first-order system with zero input (homogeneous):
Taking the unilateral Laplace transform of the original DE:
![$\displaystyle \tau\frac{d}{dt} v_c(t)+v_c(t)=0
$](img1.svg)
(
1)
we get
![$\displaystyle {\cal L}\left[\tau\frac{d}{dt} v_c(t)+v_c(t)\right]
=\tau [s V_c(s)-V_0]+V_c(s)=V_c(s)(s\tau +1)-\tau V_0=0
$](img2.svg)
(
2)
Here we have used the property
,
where
is the initial condition.
Solving for
we get
![$\displaystyle V_c(s)=\frac{\tau V_0}{s\tau+1}=\frac{V_0}{s+1/\tau}
$](img6.svg)
(
3)
The time domain voltage is the inverse transform:
![$\displaystyle v_c(t)={\cal L}^{-1}\left[\frac{V_0}{s+1/\tau}\right]=V_0 e^{-t/\tau}
$](img7.svg)
(
4)
- RC first-order system with constant input:
Taking the unilateral Laplace transform of the original DE:
![$\displaystyle \tau\frac{d}{dt} v_c(t)+v_c(t)=v_s(t)=V_s\,u(t)
$](img8.svg)
(
5)
we get
![$\displaystyle {\cal L}\left[\tau\frac{d}{dt} v_c(t)+v_c(t)\right]
=\tau [s V_c(s)-V_0] + V_c(s)={\cal L} \left[ V_s\,u(t) \right]=\frac{V_s}{s}
$](img9.svg)
(
6)
Solving for
, we get
![$\displaystyle V_c(s)=\frac{V_s}{s(s\tau+1)}+\frac{\tau V_0}{s\tau+1}
=V_s\left(\frac{1}{s}-\frac{\tau}{s\tau+1}\right)+\frac{\tau V_0}{s\tau+1}
$](img10.svg)
(
7)
Taking the inverse Laplace trannsform we get the solution of the DE in time domain:
![$\displaystyle v_c(t)={\cal L}^{-1}\left[V_c(s)\right]=V_s-V_s e^{-t/\tau}+V_0e^{-t/\tau}
=V_s+(V_0-V_s)e^{-t/\tau}
$](img11.svg)
(
8)
To find the steady state solution, we can use the final-value theorem:
![$\displaystyle \lim_{t\rightarrow\infty}v_c(t)=\lim_{s\rightarrow 0} s V_c(s)
=...
...rightarrow 0} \left[\frac{V_s}{(s\tau+1)}+\frac{\tau sV_0}{s\tau+1}\right]=V_s
$](img12.svg)
(
9)
- RC first-order system with sinusoidal input:
First consider a complex input
on the right-hand side:
![$\displaystyle \tau\frac{d}{dt} v_c(t)+v_c(t)=V_s \cos(\omega t)=V_s e^{j\omega t}\,u(t)
$](img14.svg)
(
10)
Taking the transform on both sides, we get
![$\displaystyle {\cal L}\left[\tau\frac{d}{dt} v_c(t)+v_c(t)\right]
=s\tau V_c(s...
...u V_0+V_c(s)={\cal L}\left[V_s\,e^{j\omega t}u(t)\right]=\frac{V_s}{s-j\omega}
$](img15.svg)
(
11)
Solving for
, we get
![$\displaystyle V_c(s)=\frac{1}{s\tau+1}\left(\frac{V_s}{s-j\omega}+\tau V_0\righ...
...\left(\frac{1}{s-j\omega}-\frac{1}{s+1/\tau}\right)
+\frac{\tau V_0}{s\tau+1}
$](img16.svg)
(
12)
Taking the inverse Laplace trannsform we get the solution of the DE in time domain:
Taking the real part we get the solution: